Increasing Science Learning Interest in Class VIII SMPN 2 Mataram through STEM Teaching Aids Making Practice - Ferniawan Ferniawan; Rabi'atul Adawiyah; Ewan Gunawan; Heriyanto Heriyanto (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2026)
Natural Sciences (IPA) learning at the junior high school level still faces the problem of low student learning interest due to the dominance of conventional learning and limited practicum facilities. This community service activity aims to increase the interest and motivation to learn science for grade VIII students of SMPN 2 Mataram through the practice of making STEM-based teaching aids (Science, Technology, Engineering, and Mathematics) in business and energy materials. The activity will be carried out in November 2025 by involving grade VIII students as the main participants. The implementation method includes the introduction of business and energy concepts, the practice of making simple teaching aids in groups, and evaluation through learning interest questionnaires and reflective discussions. The results showed that students were actively involved in the process of designing, manufacturing, and testing props, and showed high enthusiasm and participation during the learning process. The practice of making STEM-based props helps students understand the concepts of business and energy in a more concrete and contextual way. Based on the results of the evaluation, this activity has been proven to have a positive impact on increasing students' interest and motivation to learn science. Thus, the practice of making STEM-based teaching aids can be an effective and sustainable alternative to innovative learning to improve the quality of science learning at the junior high school level, even with limited laboratory facilities.